2019
DOI: 10.1111/and.13469
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects ofStevia rebaudianaaqueous extract on experimental unilateral testicular ischaemia/reperfusion injury in rats

Abstract: This project aimed to examine Stevia rebaudiana aqueous extract protective effects on testicular ischaemia/reperfusion injury of rats. Forty rats were randomly divided into five groups: (1) sham group, (2) torsion/detorsion group, (3 and 4) low and high doses treatment groups received S. rebaudiana extract intraperitoneally 30 min before detorsion by 500 and 1,000 mg/kg respectively, and (5) healthy group received the extract by 1,000 mg/kg. In this study, left testes were rotated 2 hr, reperfusion period took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Despite effective surgical mediation, testicular atrophy and infertility rate increased between 40% and 60% (Bozkurt et al, 2019). In addition to testicular atrophy and infertility, reduction in hormone production is another major complication (Ganjiani et al, 2020). During the torsion period and resultant ischemia, ROS is assembled in the testicular tissue, while after surgery and torsion correction, reperfusion injury occurred due to reoxygenation of blood reopening (Gökçe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite effective surgical mediation, testicular atrophy and infertility rate increased between 40% and 60% (Bozkurt et al, 2019). In addition to testicular atrophy and infertility, reduction in hormone production is another major complication (Ganjiani et al, 2020). During the torsion period and resultant ischemia, ROS is assembled in the testicular tissue, while after surgery and torsion correction, reperfusion injury occurred due to reoxygenation of blood reopening (Gökçe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Anaesthetics and citral were injected intraperitoneally with head down position in the lower left abdominal quadrant. Rats were placed in the dorsal recumbent position after anaesthesia induction (ketamine [Alfasan, The Netherlands, 80 mg/kg], xylazine [Alfasan, The Netherlands, 3 mg/kg], and midazolam [Exir Pharmaceutical Co., Iran, 3 mg/kg]) (Ganjiani et al, 2020). Immediately after anaesthesia induction, the surgical area was shaved and disinfected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study could not be detailed by hormone analyses and immune staining techniques. Testicular torsion is an urgent urological problem known since the 1800s with irreparable risks such as testicular atrophy, subfertility, fertility and endocrine disorders (Ganjiani et al., 2020). Several previously conducted clinical trials have reported that more than half of patients diagnosed with testicular torsion are under the age of 21 (Cumming et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Stevia group: For 56 days, Stevia was allowed to dissolve in water (1000 mg/kg of body weight). 17 Tartrazine group: were administrated orally by gavage Tartrazine dissolved in water (300 mg/kg body weight) for 56 days. 1,3 Stevia and Tartrazine group: were administrated orally by gavage Tartrazine after 1 h of administrating Stevia for 56 days.…”
Section: Study Design and Animalsmentioning
confidence: 99%